Incidence and Risk Factors of Hyperglycemia in Severe Multisystem Inflammatory Syndrome in Children: A Retrospective Case-Control Study - Saritas Nakip, Ozlem; Kesici, Selman; Bozkurt, Betul Seda; Ozsurekci, Yasemin; Demirbilek, Huseyin; Bayrakci, Benan (Journal of Pediatric Infectious Diseases, 2022)
Objective Multisystem inflammatory syndrome in children (MIS-C) patients might be at risk for hyperglycemia and associated complications. Herein, we aimed to determine the incidence of hyperglycemia, understanding the underlying risk factors in MIS-C patients.Methods All MIS-C patients were retrospectively evaluated and compared according to the presence of hyperglycemia and the need of insulin. Inflammatory markers and body mass index Z-scores were also compared.Results The median age of the patients with hyperglycemia was higher than those without (p = 0.001). Disease severity scores of patients with hyperglycemia were higher. Procalcitonin levels of patients with hyperglycemia were higher, while ferritin, CRP, and interleukin-6 levels were not. BMIs of patients with hyperglycemia were higher (p = 0.01) but BMI Z-scores were similar (p = 0.055). There was a positive correlation between BMIs and CRP (r: 0.31, p = 0.015). There was a positive correlation between procalcitonin (r: 0.431, p = 0.001) and CRP (r: 0.279, p = 0.029) and maximum PG.Conclusion Hyperglycemia is a common feature of MIS-C patients and is associated with the severity of the inflammation. As a novel finding, high CRP and procalcitonin should be considered as predictive markers for impaired glucose homeostasis in MIS-C patients.
Keywords: hyperglycemia; multisystem inflammatory syndrome in children; obesity; inflammation; insulin